2013
DOI: 10.2967/jnumed.112.110304
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Lymph Node Metastasis Depends on Metabolic Activity of the Primary Lesion in Thoracic Squamous Esophageal Cancer

Abstract: The metabolic activity of the primary tumor is an important variable in 18 F-FDG PET interpretation for presurgical staging, because this activity is likely to affect the possibility of detection of malignant involvement in lymph nodes (LNs). The purpose of this study was to reevaluate the diagnostic accuracy of 18 F-FDG PET/CT for the presurgical staging of esophageal squamous cell carcinoma (SCC) in correlation with the 18 F-FDG avidity of the primary lesions. Methods: One hundred fifty-six patients (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
16
2
Order By: Relevance
“…Compared with previous literatures (Manabe et al, 2013;Li et al, 2014), both the sensitivity and the specificity of FDG PET/CT are higher in this study. The reason may be related with detecting method and poor imaging based on PET with common CT or monolayer spiral CT. Additionally, the scanning slice thickness of conventional CT is 5 mm~10 mm, and the image quality is easy to be affected by partial volume effect.…”
Section: Discussioncontrasting
confidence: 84%
“…Compared with previous literatures (Manabe et al, 2013;Li et al, 2014), both the sensitivity and the specificity of FDG PET/CT are higher in this study. The reason may be related with detecting method and poor imaging based on PET with common CT or monolayer spiral CT. Additionally, the scanning slice thickness of conventional CT is 5 mm~10 mm, and the image quality is easy to be affected by partial volume effect.…”
Section: Discussioncontrasting
confidence: 84%
“…However, if the tumor SUV max was ≤2.5, it could not provide an appropriate diagnosis value for LN metastases. We attribute this result to the assumption that FDG uptake in more advanced esophageal cancers provides better diagnostic accuracy because FDG uptake of the primary lesion is positively correlated with that of LN (10,13).…”
Section: Discussionmentioning
confidence: 70%
“…Many studies have investigated the effects of NT in terms of predicting LN metastases based on the SUV max of the primary lesions and have shown success in conditions such as hepatocellular carcinoma, breast cancer, and lung cancer (10). We showed that when LN SUV max was higher than tumor SUV max , the LN was considered to be benign regardless of SUV max in non-NT and that predicting LN metastases based on the SUV max of primary lesions was possible only in non-NT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations